Anxiety prevalence among Pharmacy students during academic performance assessments in a private University in São Paulo, Brazil (Research, Society and Development, 2021)
Anxiety is considered increasing in modern society and related to academic life, especially students submitted to performance evaluations to prove good performance. The objective of this study was to determine the prevalence of anxiety in the period of academic performance evaluations, among students of the Pharmacy course of a private University in the city of São Paulo, Brazil. The study was conducted with 276 Pharmacy undergraduates, with an average age between 18 and 27 years (67%), single (59.8%) and female prevalence (74.6%). Students, before performance assessments, reported anxiety alone (64.5%) or associated with stress, worry, insomnia and impatience (63%). There was a statistically significant difference between anxious (16.9±12.2) and quiet (3.6±2.9) students before performance evaluations, with p